Adolescent Reproductive Health Counseling in The Framework of Stunting Prevention - Wiradi Suryanegara; Abitmer Gultom; Vidi Posdo A. Simarmata; Andriyani Risma Sanggu; Nia Reviani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Adolescents/teenagers are the age group from 10 years to before the age of 18 years. Efforts to maintain adolescent health aim to prepare adolescents to become healthy, intelligent, qualified, and productive adults and to participate in maintaining, maintaining, and improving their health. Adolescent health is very important to pay attention to because, during this period, teenagers experience significant physical, psychological, and social changes. Adolescent health efforts include positive development, accident prevention, violence prevention, reproductive health, prevention and control of infectious diseases and prevention of non-communicable diseases, nutrition and physical activity, mental health, and adolescent health in crises. This community service takes the topic of reproductive health to increase participants' knowledge about reproductive health. This community service method uses an educational approach through counselling with a total of 136 participants who are students of SMPN 2 Jatigede, Ciranggem Village, Sumedang Regency, West Java. Counselling is carried out by involving resource persons who are experts in their fields. The results of the counselling showed that there was a significant increase in participants' knowledge, as indicated by the results of the post-test. Participants in the